Perceptions of violence based on genetics: the influence of monoamine oxidase A in the origin of violent behavior (Research, Society and Development, 2020)
Objective: To gather scientific literature regarding the influence of the low activity of the enzyme Monoaminoxidase A, responsible for the regulation of brain neurotransmitters, on criminal and / or violent behavior. Methods: Searches were performed in the PubMed and SCOPUS databases using “genes”, “crime” and “monoaminoxidase”, selecting articles published between 2009 and 2019. Results: The selected sample, after applying the inclusion criteria and exclusion, was composed of 14 articles. Discussion: A relationship was found between low levels of activity of Monoaminoxidase A, when associated with socio-environmental factors, with a greater tendency to commit criminal and / or violent acts. Among the socio-environmental factors, the most cited is the experience of trauma in childhood. However, there were copyright disagreements, which demonstrates the need for further investigation and development of studies on the subject. Final considerations: It was found that individuals with low Monoaminoxidase A activity and who experienced stressful socioenvironmental factors are more prone to aggressive and / or violent behavior.